Awareness With Paralysis Among Critically Ill Emergency Department Patients: A Prospective Cohort Study*. Issue 10 (21st July 2022) - Fuller, Brian M.; Pappal, Ryan D.; Mohr, Nicholas M.; Roberts, Brian W.; Faine, Brett; Yeary, Julianne; Sewatsky, Thomas; Johnson, Nicholas J.; Driver, Brian E.; Ablordeppey, Enyo; Drewry, Anne M.; Wessman, Brian T.; et al.
Abstract : OBJECTIVES: In mechanically ventilated patients, awareness with paralysis (AWP) can have devastating consequences, including post-traumatic stress disorder (PTSD), depression, and thoughts of suicide. Single-center data from the emergency department (ED) demonstrate an event rate for AWP factors higher than that reported from the operating room. However, there remains a lack of data on AWP among critically ill, mechanically ventilated patients. The objective was to assess the proportion of ED patients experiencing AWP and investigate modifiable variables associated with its occurrence. DESIGN: An a priori planned secondary analysis of a multicenter, prospective, before-and-after clinical trial. SETTING: The ED of three academic medical centers. PATIENTS: Mechanically ventilated adult patients that received neuromuscular blockers. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: All data related to sedation and analgesia were collected. AWP was the primary outcome, assessed with the modified Brice questionnaire, and was independently adjudicated by three expert reviewers. Perceived threat, in the causal pathway for PTSD, was the secondary outcome. A total of 388 patients were studied. The proportion of patients experiencing AWP was 3.4% ( n = 13), the majority of whom received rocuronium ( n = 12/13; 92.3%). Among patients who received rocuronium, 5.5% ( n = 12/230) experienced AWP, compared with 0.6% ( n = 1/158) among patients who did not receive rocuronium in the ED (odds ratio, 8.64; 95% CI, 1.11–67.15). Patients experiencing AWP had a higher mean (sd ) threat perception scale score, compared with patients without AWP (15.6 [5.8] vs 7.7 [6.0]; p < 0.01). CONCLUSIONS: AWP was present in a concerning proportion of mechanically ventilated ED patients, was associated with rocuronium exposure in the ED, and led to increased levels of perceived threat, placing patients at greater risk for PTSD. Studies that aim to further quantify AWP in this vulnerable population and eliminate its occurrence are urgently needed.